The Use of “Mobile Legends” Games to Enhance Students’ Vocabulary Mastery Among Junior High School Student - Santi, Kurnia; Khatimah, Khusnul (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The objective of this is to find out the influence of the online game Mobile Legends on the vocabulary mastery among Junior High School students. The idea for this research started from initial observations that researcher made there and obtained data that most students still have difficulty writing in English and based on interviews with students, researcher obtained data that the students there were very interested in online games, namely mobile legends. Starting from this issue, researchers are interested in conducting research on the use of mobile legends in learning English. The researcher would like to find out (1) What is the students’ perception of the influence of online games on the improve of speaking skills and the addition of vocabulary in English? (2) What factors do students identify as the main barriers to getting the most out of English online games and vocabulary addition in English? The population research will be the students at eleventh grade of Vocational Junior High School Islam Syarif Hidayatullah Muara Badak. The total number of students at eighth grade will be 42. The sample of this research will be students from class VII and VIII. This research will determine the sample by using purposive sampling.